2018
DOI: 10.3389/fnins.2018.00259
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Threonine 175 Tau in the Induction of Tau Pathology in Amyotrophic Lateral Sclerosis—Frontotemporal Spectrum Disorder (ALS-FTSD). A Review

Abstract: Approximately 50–60% of all patients with amyotrophic lateral sclerosis (ALS) will develop a deficit of frontotemporal function, ranging from frontotemporal dementia (FTD) to one or more deficits of neuropsychological, speech or language function which are collectively known as the frontotemporal spectrum disorders of ALS (ALS-FTSD). While the neuropathology underlying these disorders is most consistent with a widespread alteration in the metabolism of transactive response DNA-binding protein 43 (TDP-43), in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 126 publications
3
12
0
Order By: Relevance
“…[4][5] Specifically, cytoplasmic inclusions of hyperphosphorylated tau have been described in ALS post-mortem mCTX and spinal cord. [6][7][8] Here, our results expand on these findings and demonstrate a significant mis-localization of tau and pTau-S396 from the cytosol to synapses, reminiscent of AD. 32…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…[4][5] Specifically, cytoplasmic inclusions of hyperphosphorylated tau have been described in ALS post-mortem mCTX and spinal cord. [6][7][8] Here, our results expand on these findings and demonstrate a significant mis-localization of tau and pTau-S396 from the cytosol to synapses, reminiscent of AD. 32…”
Section: Discussionsupporting
confidence: 80%
“…3 Recent studies have begun to link alteration in tau phosphorylation to ALS pathogenesis in both sporadic and familial cases, 4,5 as cytoplasmic inclusions of hyperphosphorylated tau have been described in post-mortem motor cortex (mCTX) and spinal cord from ALS patients. [6][7][8] Tau is required for the trafficking of mitochondria across the axons to the synapses, 9 a crucial event to sustain the high energy requirement of neuronal cells. Hyperphosphorylation of key epitopes on tau impairs this process and disrupts mitochondrial localization, [10][11][12][13] thus contributing to axonal dysfunction and synapse loss in Alzheimer's disease (AD).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study detected tau overexpression (Gómez-Pinedo et al, 2016); we hypothesised that this finding may be linked to increased AICD expression resulting from APP pathway activation (Kim et al, 2003; Ghosal et al, 2009). Tau overexpression has also been reported by other researchers (Vintilescu et al, 2016), and the protein’s potential role in ALS has recently been reviewed (Moszczynski et al, 2018). Our study found no correlation with Notch, however.…”
Section: Discussionmentioning
confidence: 64%
“…Tau pathology has also been described in association with ALS/MND, although tau deposition is not a feature of the typical inclusions of ALS/MND-TDP. Abnormal neuronal and glial tau phosphorylation has been suggested in the ALS/MND spectrum [5,6], but other studies have found that this is mostly low-Braak stage Alzheimer's type pathology and have not confirmed glial tau pathology [7]. A lack of predilection for enhanced tauopathy in FTLD-TDP, and of TDP-43 in FTLD-tau, suggests a lack of direct interaction [8].…”
Section: Introductionmentioning
confidence: 98%